River restoration and dam removal in the American West: an examination of policy change across political jurisdictions - Clark, Bradley T., author; Davis, Charles E., advisor (Colorado State University. Libraries, 2007)
The engineering of water resources has largely defined the advance of civilization in North America. For various purposes, this development has continually expanded, with emphasis on societal benefits often at the expense of ecological considerations. The heyday of dam building ended by the mid-1960s, with the largest structures being completed. Since then, environmental and social impacts have mounted in severity and scope. For decades, research from the natural sciences has documented many negative ecological impacts from the damming of rivers. More recently, a political movement to restore rivers and natural resources has grown and prompted numerous changes to traditional polices of river development. This dissertation's focus is dam removal, an example of such policy change, and means to restore rivers in the western US. The theoretical perspective offered by Lowry (2003) is utilized to examine policy change and explore the political dimensions of dam removal. Key variables include the degrees of political receptivity and physical complexity of proposed dam removals. Specific attention is on the three federal jurisdictional contexts in which the political debates unfold; these include dams under the direction of the US Army Corps of Engineers; the US Bureau of Reclamation; and nonfederal hydropower dams regulated by the Federal Energy Regulatory Commission. A detailed case from each context examines the political dynamics and address the question of why dams in some contexts have been removed or are slated for removal, while others have not. A fourth, intergovernmental context is also considered for dams under the primary jurisdiction of a state or local administrative agency, albeit with notable federal influence and/or involvement. Broad research questions include: How do the politics of dam removal play out in different political jurisdictions? Are dramatic versus less dramatic types of policy change more or less likely in various contexts? This research finds that major policy change can occur, not only within federal administrative contexts in the West, but for cases when political receptivity is low and physical complexity is high.
Keywords: dam removal; policy change; political jurisdictions; river restoration; public administration; environmental science